The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.xphs.2020.09.051
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Ocular and Systemic Pharmacokinetics of Brinzolamide in Rabbits After Intracameral, Topical, and Intravenous Administration

Abstract: Brinzolamide is a topical carbonic anhydrase inhibitor which reduces the production of aqueous humor in the ciliary body, thereby reducing intra-ocular pressure. It is formulated as an ophthalmic suspension. The pharmacokinetics of ocular suspensions is not well understood. The objective of this study was to characterize the pharmacokinetics of brinzolamide in rabbit aqueous humor, iris-ciliary body, plasma, and whole blood. New Zealand White rabbits were dosed via intracameral, topical and intravenous adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…A similar trend was observed with intracameral timolol, with approximately 16% of the drug eliminating via the AH outflow resulting in a half-life of 33.64 min in rabbit eyes (Fayyaz et al, 2020a). Another study suggested the importance of high drug binding of intracameral brinzolamide to tissues, such as, the iris-ciliary body (Naageshwaran et al, 2020). Development of IVIVCs for CL of hydrophobic drugs from the vitreous cavity was previously demonstrated due to the lack of an RCS pathway with the previous PK-Eye ™ prototype (Awwad et al, 2017b).…”
Section: Discussionsupporting
confidence: 57%
“…A similar trend was observed with intracameral timolol, with approximately 16% of the drug eliminating via the AH outflow resulting in a half-life of 33.64 min in rabbit eyes (Fayyaz et al, 2020a). Another study suggested the importance of high drug binding of intracameral brinzolamide to tissues, such as, the iris-ciliary body (Naageshwaran et al, 2020). Development of IVIVCs for CL of hydrophobic drugs from the vitreous cavity was previously demonstrated due to the lack of an RCS pathway with the previous PK-Eye ™ prototype (Awwad et al, 2017b).…”
Section: Discussionsupporting
confidence: 57%
“…The PK data were analyzed using the PKSolver 2.0 add-in program for Microsoft Excel as previously described. A standard NCA was employed using mean drug concentration to estimate the area under the curve (AUC 0–∞ ) using the linear trapezoidal method, the terminal half-life ( T 1/2 ), the volume of distribution at the steady state (V d ), and vitreous clearance (Cl ivt ). NCA allows the estimation of the PK parameters directly from the measured concentrations with fewer assumptions regarding body compartments , and has been employed to estimate the ocular PK of many small and large molecules. As only one data point was obtained from each animal, the PK parameters are reported as mean values. The variance and standard deviation AUC 0–∞ were calculated using previously reported methods for calculating standard deviation for PK studies with destructive measurement techniques. …”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the clearance will be faster for lipophilic drugs more able to cross the BAB than hydrophilic drugs (Figure 2) (Fayyaz et al, 2020a;Fayyaz et al, 2020b). Drug diffusion from the irisciliary body back to the aqueous humor is unlikely for lipophilic drugs but may occur for compounds that are hydrophilic or have low permeability properties across biological membranes (e.g., atenolol or brinzolamide) (Fayyaz et al, 2020a;Naageshwaran et al, 2021).…”
Section: Corneal Absorption Routementioning
confidence: 99%
“…Intracameral pharmacokinetic studies (drug injection into the anterior chamber) can provide a better understanding of topical drug kinetics and allow the calculation of the absolute aqueous humor bioavailability of topical drugs; this has been demonstrated to be typically less than 4% (Fayyaz et al, 2020b;Naageshwaran et al, 2021;Naageshwaran et al, 2022). After intracameral injection, the same kinetic pathways shown in Figure 3 are present with the obvious exclusion of pathway 1 (corneal absorption).…”
Section: Corneal Absorption Routementioning
confidence: 99%